Clinical and Prognostic Characteristics of 53 Cases of Extracranial Malignant Rhabdoid Tumor in Children. A Single‐Institute Experience from 2007 to 2017. (26th March 2019) - Cheng, Haiyan; Yang, Shen; Cai, Siyu; Ma, Xiaoli; Qin, Hong; Zhang, Weiping; Fu, Libing; Zeng, Qi; Wen, Mingjie; Peng, Xiaoxia; Wang, Huanmin
Abstract: Background: The aim of this study is to add to the current knowledge regarding extracranial malignant rhabdoid tumor (MRT), a rare and highly aggressive tumor that occurs most commonly in infants and young children. Patients and Methods: A retrospective medical record review was conducted on 53 patients with pathologically confirmed MRT in Beijing Children's Hospital between January 2007 and October 2017. Results: Fifty‐three patients were diagnosed with MRT at a median age of 16 months, including 32 cases of malignant rhabdoid tumor of the kidney (MRTK) and 21 cases of extrarenal extracranial rhabdoid tumor (EERT). Fourteen (14/32, 43.75%) patients with MRTK and five (5/21, 23.81%) patients with EERT had metastases at diagnosis, and quite a few number of cases occurred tumor rupture (26.42%). Among the 53 patients, 40 (75.47%) patients died, 10 (18.87%) patients survived, and 3 patients (5.66%) were lost to follow‐up. Among the 40 dead patients, 38 patients died from rapid progression of the disease or tumor recurrence, and 2 patients died of severe postoperative complications. Most of the recurrent or relapsed cases (94.11%) occurred within 8 months, with a median time of 76 days after diagnosis. The overall survival rates of 3 years and 5 years for the entire cohort were 23.71% and 18.44%, respectively. After survival analysis, it was clear that a younger age at diagnosis and distant stage patients had relatively poor outcomes. The effect of treatment was the most difficult to analyze because patients were not treated uniformly. Statistically significant differences in survival were noted among patients treated with standard chemotherapy, total resection, and radiotherapy. Conclusion: Extracranial MRT is still a highly aggressive tumor in children. Younger patients and those suffering from metastatic disease were most likely to have a poor outcome because of rapid progression or recurrence of the tumor. Abstract : Extracranial malignant rhabdoid tumor (MRT) is a rare and aggressive tumor that occurs mainly in infants and young children. This review reports the clinical characteristics, treatment schedules, and outcomes of patients with MRT from a single institution in China.